Thyroid diseases are associated with coronavirus disease 2019 infection - Tian, Yutian; Zhao, Junyu; Wang, Tingting; Wang, Haipeng; Yao, Jinming; Wang, Song; Mou, Yaru (Frontiers in Endocrinology, 2022)
Background In 2019, there was a global outbreak of new coronary pneumonia. Studies have found that the severity of patients with new coronary pneumonia may be related to their comorbidities. This article discusses the impact of thyroid disease on the severity of new coronary pneumonia through a meta-analysis and provides new treatment ideas for the later treatment and recovery of new coronary pneumonia. Methods Databases including PubMed, Embase, Cochrane Library, SINOMED, China national knowledge infrastructure (CNKI), and Wanfang for coronavirus disease 2019 (COVID-19) infection and thyroid diseases were searched. Reference lists of all eligible articles and related previous review articles were handsearched. Fifty-three articles were included to conduct the meta-analysis. Results Fifty-three articles with 12,022 COVID-19 infection patients were included in this meta-analysis. The proportion of patients with thyroid diseases in all COVID-19 infection patients fluctuates between 0% and 88.46%. Of the 53 included studies, 22 studies reported the severity of COVID-19 infection and grouped. The fixed-effects model was used to merge odds ratio (OR) values, and the pooled effect size in favor of non-severe patients is 2.62 (95% CI = 1.96–3.49, P < 0.0001), which means that patients with severe COVID-19 infection are more likely to have thyroid diseases. The analysis subgrouped into Asia and Europe shows that patients with COVID-19 severe infection in Asia are 3.77 times more likely to have thyroid diseases than non-severe patients (fixed-effects model: OR = 3.77, 95% CI = 2.66–5.35, P < 0.00001). No significant statistical heterogeneity was found by the heterogeneity analysis (chi-square = 19.85, P = 0.34, I2 = 9%). Severe COVID-19 infection patients are more likely to be complicated by hypothyroidism and low T3 syndrome. The pooled ORs with fixed-effects model are 3.72 (95% CI = 1.62–8.58, P = 0.002) and 5.86 (95% CI = 2.79–12.33, P < 0.00001), respectively. Conclusion COVID-19 infection patients with thyroid diseases are very common, and severe patients are more likely to have thyroid diseases. Asian COVID-19 infection, hypothyroidism patients, and patients with low T3 syndrome are more likely to progress to severe condition. Systematic Review Registration https://inplasy.com, identifier INPLASY202190079.